Differential accumulation of manganese in three mature tree species (Holoptelia, Cassia, Neem) growing on a mine dump - Raju, D.; Kumar, Sunil; Mehta, Urmil J.; Hazra, Sulekha (Current Science, 2008)
Three trees, including Cassia siamea (Cassia), Azadirachta indica (Neem), Holoptelia integrifolia (Holoptelia) belonging to three different families were identified from a manganese mine tailing dump. Manganese content in dump soil and in the stem, green leaves and dry, fallen leaves of the plants was determined. Values were compared with similar samples collected from normal vegetation. Under control condition, manganese content was highest in Cassia. Distribution of metal in samples collected from the dump site revealed that Holoptelia has a special ability to accumulate high amounts of manganese under stress condition followed by Cassia and Neem. There is no literature on metal accumulation in Holoptelia. Mechanism of manganese sequestration in Holoptelia is different from the other two trees growing in the same soil.
Keywords: Azadirachta indica; Cassia siamea; Holoptelia integrifolia; hyperaccumulator; manganese; mine dump

Synthesis of gold nanoparticles by various leaf fractions of Semecarpus anacardium L. tree - Raju, D.; Mehta, Urmil J.; Hazra, Sulekha (Trees-Structure and Function, 2011)
Gold nanoparticles (NPs) were synthesized using Semecarpus anacardium leaf extracts in water and the green biomass. Extract prepared at ambient condition by crushing the leaves in deionized water is identified as `green extract', and that by boiling the leaf pieces as `boiled extract'. The mass remaining after separating the `green extract' is identified as `green biomass'. These components triggered rapid reduction of Au(III) to Au (0) in HAuCl4 solution indicating the natural ability of the leaves of S. anacardium to synthesize NPs in ambient conditions. Green extract produced more NPs compared to the boiled extract suggesting denaturization of some of the useful factors due to boiling. NPs were quantified using UV and ICP-AES analysis. These were characterized using Transmission electron microscopy, Fourier transform infrared spectroscopy and X-ray diffraction. TEM images of the particles formed with green extract, boiled extract and green biomass showed that the particles were of different shapes and sizes.
Keywords: Biosynthesis; gold nanoparticles; Green extract; Semecarpus; TEM

Extra- and intracellular gold nanoparticles synthesis using live peanut callus cells - Raju, D.; Mehta, Urmil J.; Ahmad, Absar (Current Nanoscience, 2013)
An important challenge of considerable topical significance in nanotechnology is the development of eco-friendly experimental processes for the synthesis of nanomaterials in large quantities with variable sizes, shapes and chemical compositions. Green synthesis routes for the production of inorganic metal nanoparticles using whole cell of microorganisms and plant extracts are gaining tremendous popularity as these are non-toxic, cheap and occur at ambient conditions. The present work emphasizes on gold nanoparticles synthesis protocol using live plant callus cells. Peanut callus cells when incubated with HAuCl4 solution in ambient conditions reduced the precursor and lead to formation of well dispersed, water soluble extracellular and intracellular gold nanoparticles within 24 hours. The biosynthesis of gold nanoparticles was monitored by UV-visible spectroscopy (UV-Vis) and further characterized by X-ray diffraction analysis (XRD), Energy Dispersive Spectroscopy (EDS) and Selected Area Electron Diffraction (SAED). The particle size distribution shows that the average particle size is 50 nm for extra-and 31 nm for intracellular gold nanoparticles. The nanoparticles may be stabilized by proteins secreted by callus cells. The reduction process is believed to occur enzymatically, thus creating the possibility of a rational, plant cell-based method for the synthesis of nanoparticles over a wide range of chemical compositions.
Keywords: Biosynthesis; callus; gold nanoparticles; live cells; Peanut; TEM

Phytosynthesis of silver nanoparticles by semecarpus anacardium L. leaf extract - Raju, D.; Hazra, Sulekha; Mehta, Urmil J. (Materials Letters, 2013)
Green synthesis of silver nanoparticles (AgNPs) using Semecmpus anacardium L leaf extract was studied. The reduction of silver (Ag+) ions was characterized by using UV-vis spectrophotometer showing formation of AgNPs within 15-20 mm. A time dependent reaction showed the increase in the nanoparticles (NPs) with time. Transmission electron microscopy (TEM) analysis showed that the synthesized AgNPs varied from 10 to 25 nm and has spherical shape. The Fourier transform infrared (FTIR) analysis showed that phenols and protein were responsible for the formation of the AgNPs. The energy dispersive spectroscopy (EDAX) analysis confirms the formed NPs were of silver. The quantification of AgNPs was studied by inductive coupled plasma spectrometry (ICP-AES). The important outcome of this work can be value addition to the medicinal plants in synthesis of NPs for biomedical applications. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: FTIR; Leaf extract; Nanoparticles; Semecarpus anacardium; synthesis; TEM

Synthesis of Ag-glyconanoparticles using C-glycosides, their lectin binding studies and antibacterial activity - Ramtenki, Vilas; Raju, D.; Mehta, Urmil J.; Ramana, C. V.; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2013)
Two 12-C-glycosyl dodecanoic acids, namely, 1-(alpha-D-mannopyranosyl)-12-dodecanoic acid and 1-(alpha-D-glucopyranosyl)-12-dodecanoic acid were synthesized. Their ability to act as reducing and capping agents for the synthesis of water re-dispersible silver nanoparticles is displayed. These Ag C-glycosyl nanoparticles were later utilized to investigate the carbohydrate-lectin interactions. Furthermore, the specificity of mannoside binding to the surface of the Gram negative bacterium Escherichia coli has been utilized to demonstrate the enhanced antibacterial activity of Ag-C-mannosyl nanoparticles towards this bacterium as compared to Ag-C-glycosyl nanoparticles.

Biological synthesis of cationic gold nanoparticles and binding of plasmid DNA - Raju, D.; Vishwakarma, Rishi K.; Khan, Bashir Mohammad; Mehta, Urmil J.; Ahmad, Absar (Materials Letters, 2014)
Nanobiotechnology is the development of eco-friendly experimental processes for the synthesis of nanomaterials. The present work focuses on synthesis of cationic gold nanoparticles (C-GNPs) for biological applications, especially in gene and drug delivery studies. A biosynthesis methodology has been developed for the functionalization of gold nanoparticles to cationic nature. The synthesis of C-GNPs was done by using peanut leaf extract in the presence of cysteamine. The formed C-GNPs were characterized by using UV-visible spectroscopy (UV-vis), the particles sizes and shapes were confirmed by a Transmission electron microscope (TEM) and crystallinity of C-GNPs was characterized by diffraction. The binding of plasmid DNA on the C-GNPs was confirmed by agarose gel electrophoresis. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Biomaterials; Cationic; Nanoparticles; Plasmid DNA; synthesis; TEM

Extracellular synthesis of silver nanoparticles using living peanut seedling - Raju, D.; Paneliya, Nikita; Mehta, Urmil J. (Applied Nanoscience, 2014)
Synthesis of nanoparticles by environment friendly method is an important aspect of nanotechnology. In the present study, extracellular reduction of silver ions to silver nanoparticles was carried out using living peanut plant. The electron microscopic analysis shows that the formed nanoparticles were of different shapes and sizes. The formed nanoparticles were polydispersed. The shapes of the nanoparticles were spherical, square, triangle, hexagonal and rod. Most of the particles were spherical and 56 nm in size. EDS analysis confirmed the formed nanoparticles were of silver. The crystalline nature of nanoparticles was confirmed by diffraction. This method opens up an exciting possibility of plant-based synthesis of other inorganic nanomaterials. This study confirms the synthesis of extracellular silver nanoparticles by living plant.
Keywords: Nanoparticles; Shapes; Silver; synthesis; TEM

Living plant-mediated synthesis of different shaped gold nanoparticles - Raju, D.; Paneliya, Nikita; Mehta, Urmil J. (Nanoscience and Nanotechnology Letters, 2014)
We demonstrate extracellular green synthesis of gold nanoparticles with different shapes and sizes by using live Prosopis juliflora L. seedling. The conversion of ionic to metallic gold nanoparticles by P. juliflora seedling was carried out in short period. The formed nanoparticles were characterized by UV, TEM, Diffraction and EDS. TEM shows well dispersed particles of different shapes and sizes. The percentage of different shapes of nanoparticles was calculated, most of the particles were spherical in shape (75%). The triangle nanoparticles were 10%, followed by squares (8%), hexagonal (5%) and rods (2%). The diffraction shows the formed nanoparticles are crystalline in nature and EDS confirms the formed nanoparticles are of gold. This shows P. juliflora seedling can synthesis different shapes of well dispersed nanoparticles.
Keywords: Gold; Nanoparticles; Prosopis juliflora; Shapes; synthesis; TEM

Protein mediated synthesis of Au-Ag bimetallic nanoparticles - Raju, D.; Mendapara, Ritul; Mehta, Urmil J. (Materials Letters, 2014)
There is growing need to develop environment friendly method for synthesis of bimetallic nanoparticle that do not use toxic chemicals during their synthesis process. Here, we report synthesis of Au-Ag bimetallic nanoparticles by using macerase enzyme as reducing agent at different temperatures. Bimetallic nanoparticles were synthesized at 80 and 90 degrees C. The intensity of formation of nanoparticles was more at 80 degrees C. The bimetallic nanoparticles are characterized by using UV-vis, TEM and EDAX. The TEM study shows the inner gold and outer silver bimetallic nanoparticles. The formed nanoparticles are 4-20 nm in size and spherical in shape. EDAX confirms the formed bimetallic nanoparticles are of gold and silver. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Enzyme; Gold; Macerase; Particles; Silver; synthesis

Simple recovery of intracellular gold nanoparticles from peanut seedling roots - Raju, D.; Mehta, Urmil J.; Ahmad, Absar (Journal of Nanoscience and Nanotechnology, 2015)
Fabrication of inorganic nanomaterials via a biological route witnesses the formation either extracellularly, intracellulary or both. Whereas extracellular formation of these nanomaterials is cherished owing to their easy and economical extraction and purification processes; the intracellular formation of nanomaterials, due to the lack of a proper recovery protocol has always been dreaded, as the extraction processes used so far were tedious, costly, time consuming and often resulting in very low recovery. The aim of the present study was to overcome the problems related with the extraction and recovery of intracellularly synthesized inorganic nanoparticles, and to devise a method to increasing the output, the shape, size, composition and dispersal of nanoparticles is not altered. Water proved to be much better system as it provided well dispersed, stable gold nanoparticles and higher recovery. This is the first report, where intracellular nanoparticles have been recovered using a very cost-effective and eco-friendly approach.
Keywords: gold nanoparticles; Peanut; Recovery; Sonication; Water

Identification of biomolecules involved in the biosynthesis of gold nanoparticles from living peanut seedlings - Raju, D.; Siddiqui, Ejaz Ahmad; Prasanth, S.; Khan, Bashir M.; Mehta, Urmil J.; Ahmad, Absar (Journal of Nanoscience and Nanotechnology, 2017)
In present work, we have fabricated gold nanoparticles by treating an aqueous solution of 10(-4) M HAuCl4 with the proteins extracted from roots of in vitro raised peanut seedlings and purified them by FPLC at room temperature. These proteins which tested positive for the reduction of 10(-4) M HAuCl4 were identified as Mannose glucose binding lectin and Ara h 8 allergen isoforms by ESI MS/MS. It is a well known fact that aromatic amino acids possess delocalized pi electrons in their ring structures, rendering them as the best electron donors which can transfer electrons and reduce the acceptor. These results suggest that the aromatic amino acids present in the proteins from the peanut seedlings are the primary biomolecules involved in the reduction of Au (III) to Au (0). We isolated different protein of molecular weight 16.4, 28.3 and 30 kDa involved in the formation of nanoparticles. The protein with molecular weight 16.4 kDa (allergens) yielded NPs of 25-60 nm whereas, the proteins with molecular weight 28.3 kDa and 30 kDa (lectins) yielded highly monodispersed NPs of 5-20 nm in size. The results clearly indicate that the size of nanoparticles can be controlled by different proteins.